2004
DOI: 10.1007/s00415-004-0532-y
|View full text |Cite
|
Sign up to set email alerts
|

Contraversive pushing in non-stroke patients

Abstract: The results demonstrate that contraversive pushing may also occur in patients with non-stroke neurological lesions and suggest that resolution of symptoms may vary according to the underlying etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1
8

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 8 publications
0
25
1
8
Order By: Relevance
“…Among the studies that considered the PB according to Davies' description, the incidence of this disorder ranges from 1.5 % to 63 % of patients with acute encephalic lesions (Table 1) (Pedersen et al, 1996;Danells et al, 2004;Santos-Pontelli et al, 2004;Lafosse et al, 2005;Baccini et al, 2006). Pedersen et al (Pedersen et al, 1996) found an incidence of 5.3 % of PB in all stroke patients who were admitted in study period and 10.4 % of patients without lower extremity paresis on admission, when early death or early recovery were excluded.…”
Section: Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…Among the studies that considered the PB according to Davies' description, the incidence of this disorder ranges from 1.5 % to 63 % of patients with acute encephalic lesions (Table 1) (Pedersen et al, 1996;Danells et al, 2004;Santos-Pontelli et al, 2004;Lafosse et al, 2005;Baccini et al, 2006). Pedersen et al (Pedersen et al, 1996) found an incidence of 5.3 % of PB in all stroke patients who were admitted in study period and 10.4 % of patients without lower extremity paresis on admission, when early death or early recovery were excluded.…”
Section: Incidencementioning
confidence: 99%
“…Thus, the listing phenomenon, thalamic astasia and Wallenberg's syndrome need to be considered in the differential diagnosis of PB. Although the PB was originally described in association with neglect and anosognosia as a syndrome that is related to right encephalic lesions by the physical therapist Davies (Davies, 1985), several studies have demonstrated that it can occur in patients with lesions in both hemispheres and is distinct from those neuropsychological deficits (Pedersen et al, 1996;Karnath et al, 2000bKarnath et al, , 2000aPremoselli et al, 2001;Pérrenou, 2002;Bohannon, 2004;Santos-Pontelli et al, 2004). Since the definition of 'syndrome' is "a set of qualities, events or behaviors that is typical of a particular kind of problem' (Longman dictionary of Contemporary English; 1995) and the diagnostic criteria for PB are presence of the 3 behaviors observed by the examiner described above, the term 'pusher syndrome' can be considered appropriate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a study carried out in our neurological emergency unit we identified the association of Pusher syndrome and other etiologies (cranial trauma and cerebral metastases), with times of resolution that were apparently briefer 12 .…”
Section: Introductionmentioning
confidence: 97%
“…This syndrome was initially described by Davies, in 1985, who suggested the association of cerebral vascular accidents (CVA) on the right hemisphere and neuropsychological symptoms of heminegligence and anosognosia as part of this syndrome 9 . Later studies in patients with Pusher syndrome allowed the dissociation of posture control of neuropsychological symptoms and found frequent left side damage [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%